2005
DOI: 10.1177/0040517505057637
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Plasma Modification of Natural Fiber Fabrics-The Effect on Fabric Surface and Mechanical Properties

Abstract: Following previous work [ Textile Research Journal, 74,751-756 (2004)], the mechanical and surface properties and handle of wool and cotton fabrics were measured using the KES-FB system after different stages of treatment. This investigation shows that the mechanical properties of wool and cotton changed remarkably after oxygen plasma treatment. There were no significantly observed differences between plasma treated and untreated fabrics after wet scouring and dyeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 8 publications
6
69
2
Order By: Relevance
“…The breaking strength and elongation of textiles practically do not change (Figure 9 and 10) [3,27]. These results are in accordance with the results obtained by other authors [82][83][84][85]. Plasma modification of textiles does not impair their mechanical properties.…”
Section: Resultssupporting
confidence: 89%
“…The breaking strength and elongation of textiles practically do not change (Figure 9 and 10) [3,27]. These results are in accordance with the results obtained by other authors [82][83][84][85]. Plasma modification of textiles does not impair their mechanical properties.…”
Section: Resultssupporting
confidence: 89%
“…16 EMT has a good correlation with fabric handle. The greater the value of EMT, the larger the elongation of the fabric under a known applied stress will be.…”
mentioning
confidence: 86%
“…LT is the linearity of the load/extension curve, which reflects the elasticity of the fabric, i.e., the higher the value, the stiffer the material will be. 16 LT value equal to 1.0 indicates that the stress-strain curve rising below a 45 is a straight line. 17 Moreover, WT is also known as tensile work, which is defined as the energy required for extending a fabric, i.e., the ability of a fabric to withstand external stress during extension.…”
Section: Tensile Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Modification and functionalization of textile materials through plasma treatments have a great potential in future. The mechanical and surface properties and handle of wool and cotton fabrics after different stages of treatment using the KES-FB system by were studied by [3]. The investigation revealed that remarkable changes in mechanical properties of wool and cotton took place after oxygen plasma treatment.…”
Section: Literature Reviewmentioning
confidence: 99%